PENGARUH SUPLEMENTASI VITAMIN D TERHADAP KADAR HDAC2 PADA PASIEN PPOK STABIL - Adyan Donastin; Danny Irawan; Effendy; Rifky Dwi Aditya Iryawan; Nuzlan Nuari; Betta Mega Oktaviana; Devy Yahya; Akbar Reza Muhammad (LPPM Universitas Abdurrab, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of global mortality, characterised by persistent lung inflammation partly associated with reduced levels of histone deacetylase 2 (HDAC2). Since vitamin D may theoretically modulate HDAC2, this preliminary study aimed to evaluate the effect of vitamin D supplementation on HDAC2 levels in stable COPD patients at Jemursari Islamic Hospital, Surabaya. A one-group pre–post test experimental design without a control group was used. Five stable COPD patients meeting the inclusion criteria received 5000 IU of cholecalciferol daily for three months, with serum 25(OH)D₃ and HDAC2 measured before and after the intervention by ELISA and analysed using a paired t-test (p<0.05 considered significant). Supplementation significantly increased 25(OH)D₃ (7.63 ± 2.73 to 14.26 ± 2.43 ng/mL; p=0.023) and HDAC2 (1.50 ± 1.02 to 3.90 ± 1.39 ng/mL; p=0.006), whereas all pulmonary function parameters showed only an increasing trend without reaching statistical significance (all p>0.05). Vitamin D supplementation was associated with increased HDAC2, suggesting a potential molecular anti-inflammatory effect not yet accompanied by significant functional improvement. Given the very small sample (n=5) and the absence of a control group, these findings are hypothesis-generating and require confirmation in larger controlled trials before vitamin D can be considered as adjunctive COPD therapy.